The correlation between ferritin level and cardiac dysfunction in patients with thalassemia - Fajar Subroto; Bulan Ginting Munthe; Najib Advani; Agus Firmansyah (Indonesian Pediatric Society Publishing House, 2016)
Background Patients with b-thalassemia major, long-term trans- fusion, extravasal hemolytic, and increased intestinal absorption of iron result in systemic iron overload, which may accumulate in myocardium causing cardiac dysfunctions. Congestive heart fail- ure usually develops in adolescence or early adult years, and pa- tient usually dies within 1 year after the onset of symptoms. There- fore, it is important to detect early signs of cardiac dysfunction in patient with thalassemia. Objective This study aimed to assess the correlation between ferritin level and cardiac dysfunction in patients with thalassemia. Methods A cross sectional study was conducted on 62 b-thalas- semic patients (34 males and 28 females) with age ranging from 3.5 to 23 years. They received 3,150 - 94,985 mL of blood; with the serum ferritin level of 812.2 - 12,175 ng/mL. Each patient un- derwent laboratory examinations and clinical cardiac evaluation with ECG and echocardiography. Results Cumulative blood transfusions correlated well with the serum ferritin values (p=0.001). The serum ferritin level did not show correlation with deferoxamine (DFO) treatment. ECG exami- nation revealed 5 patients (8.1%) with dysrhythmia, LVH, and heart block grade II and I. Echocardiography examination showed 18 patients (29%) with systolic or diastolic dysfunction. There was no correlation between the serum ferritin level and cardiac dysfunc- tions (p=0.640). The serum ferritin prediction value against car- diac dysfunctions could not be established. Conclusion There was no correlation between serum ferritin lev- els with cardiac dysfunctions. In detecting cardiac dysfunctions in thalassemic patients, echocardiography was more sensitive than ECG